2010
DOI: 10.1534/genetics.110.120691
|View full text |Cite
|
Sign up to set email alerts
|

RecG Protein and Single-Strand DNA Exonucleases Avoid Cell Lethality Associated With PriA Helicase Activity inEscherichia coli

Abstract: Replication of the Escherichia coli chromosome usually initiates at a single origin (oriC) under control of DnaA. Two forks are established and move away in opposite directions. Replication is completed when these meet in a broadly defined terminus area half way around the circular chromosome. RecG appears to consolidate this arrangement by unwinding D-loops and R-loops that PriA might otherwise exploit to initiate replication at other sites. It has been suggested that without RecG such replication generates 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 92 publications
2
68
1
Order By: Relevance
“…These results suggest that, even in the presence of a functional NER system, recombinational repair (recA, ruvABC, recG, and recBCD), transcriptioncoupled repair (mfd), and repair of arrested replication forks (recG, priA) play a significant role in the repair of UV damage in N. gonorrhoeae, but not in B. burgdorferi. No orthologs of sbcCD (70) are found in the sequenced genome of N. gonorrhoeae, but their disruption did not affect B. burgdorferi survival to UV damage. Other recent studies have also reported that B. burgdorferi recA and ruvA are dispensable for repairing UV-induced DNA damage (39,40).…”
Section: Figmentioning
confidence: 97%
“…These results suggest that, even in the presence of a functional NER system, recombinational repair (recA, ruvABC, recG, and recBCD), transcriptioncoupled repair (mfd), and repair of arrested replication forks (recG, priA) play a significant role in the repair of UV damage in N. gonorrhoeae, but not in B. burgdorferi. No orthologs of sbcCD (70) are found in the sequenced genome of N. gonorrhoeae, but their disruption did not affect B. burgdorferi survival to UV damage. Other recent studies have also reported that B. burgdorferi recA and ruvA are dispensable for repairing UV-induced DNA damage (39,40).…”
Section: Figmentioning
confidence: 97%
“…The prediction is that, if performed in the recBC sbcA or recBC sbcBC backgrounds, such a screen should yield all other known rec mutants, as well as (hopefully) some still unknown ones. As an approach, identification of synthetic lethal mutant combinations shows its power in unraveling complicated pathways of the DNA metabolism around recombinational repair (270, 357), although care should be exercised with interpretation of quadruple and quintuple mutants, as the comfort zone of typical human thinking is limited to three dimensions.…”
Section: Genetic Analysis Of Hr Reveals Distinct Pathwaysmentioning
confidence: 99%
“…Also, our present and previous results suggest that the nuclease action on 3 -ssDNA is particularly important as a stimulator of ExoV activity during "reckless" DNA degradation. Such a notion is corroborated by the accumulated genetic data indicating that ExoI, ExoVII and SbcCD play partially redundant roles in removing 3 -ssDNA tails [27,30,31,[49][50][51]. ExoVII possesses both 3 -5 and 5 -3 polarities on ssDNA [45], which makes it possible that either of its activities is involved in the regulation of "reckless" DNA degradation.…”
Section: Discussionmentioning
confidence: 92%
“…Several genetic studies suggest that ExoVII plays an overlapping role with ExoI and/or SbcCD in removing 3 -ended single-stranded tails from DNA duplexes [29,31,[49][50][51]. Hence, these results indicate that ExoVII activity might also influence the extent of "reckless" degradation in recA cells.…”
Section: Effect Of Exovii Inactivation On "Reckless" Dna Degradation mentioning
confidence: 83%